Mice lacking the kf-1 gene exhibit increased anxiety- but not despair-like behavior - Tsujimura, Atsushi; Matsuki, Masato; Takao, Keizo; Yamanishi, Kiyofumi; Miyakawa, Tsuyoshi; Hashimoto-Gotoh, Tamotsu (Frontiers in Behavioral Neuroscience, 2008)
KF-1 was originally identified as a protein encoded by human gene with increased expression in the cerebral cortex of a patient with Alzheimer’s disease. In mouse brain, kf-1 mRNA is detected predominantly in the hippocampus and cerebellum, and kf-1 gene expression is elevated also in the frontal cortex of rats after chronic antidepressant treatments. KF-1 mediates E2-dependent ubiquitination and may modulate cellular protein levels as an E3 ubiquitin ligase, though its target proteins are not yet identified. To elucidate the role of kf-1 in the central nervous system, we generated kf-1 knockout mice by gene targeting, using Cre-lox recombination. The resulting kf-1−/− mice were normal and healthy in appearance. Behavioral analyses revealed that kf-1−/− mice showed significantly increased anxiety-like behavior compared with kf-1+/+ littermates in the light/dark transition and elevated plus maze tests; however, no significant differences were observed in exploratory locomotion using the open field test or in behavioral despair using the forced swim and tail suspension tests. These observations suggest that KF-1 suppresses selectively anxiety under physiological conditions probably through modulating protein levels of its unknown target(s). Interestingly, kf-1−/− mice exhibited significantly increased prepulse inhibition, which is usually reduced in human schizophrenic patients. Thus, the kf-1−/− mice provide a novel animal model for elucidating molecular mechanisms of psychiatric diseases such as anxiety/depression, and may be useful for screening novel anxiolytic/antidepressant compounds.